Eliciação, especificação e validação de requisitos de software com stakeholders surdos utilizando língua de sinais - Silva, Antônio Carlos de Freitas (2017)
About 5% of worldwide population is deaf, and for this reason Sign Language (SL) is their natural language. The LS is not limited to communication, it is also important for learning, access to information, cultural and social interactions. A Systematic Literature Review (SR) in order to identify the papers in Software Engineering with deafs. The results of SR presents a gap in Requirements Engineering with deaf stakeholders. This work presents a approach the process for Requirements Engineering with deaf stakeholders using SL, your natural language. In development of this paper, a research group was created, containing researchers of Instituto de Informática (INF/UFG) and Faculdade de Letras (FL/UFG). This group counted with Sign Language Traders and Interpreters (TILS) and a deaf deaf teacher. The study case was a software to manage the tickets of TILS in UFG, the name is Central dos Intérpretes.